Superdosing Phytases in the Diets of Light Laying Hens: Productive Performance and Bone Quality - Farias,MRS (2021)
ABSTRACT Two experiments were carried out with the objective of evaluating the effect of superdosing of two phytases on performance, egg quality, digestive organ biometry and bone quality of light hens in the first (58 weeks) and second (87 weeks) productive cycle. In the first cycle, 270 light hens were used, in which a completely randomized design was adopted in a 2 x 2 + 1 factorial scheme (bacterial phytase or fungal phytase x 450 FTUs or 900 FTUs + control diet). In the second cycle, 270 hens were used, following the same design as the previous experiment. The performance and quality of the eggs were evaluated in both cycles, and the biometry of the digestive organs and bone characteristics were also evaluated in the first experiment. There was no effect in the comparison between the means for the performance and egg quality (in both experiments), or for the biometric variables and bone characteristics (first experiment). There was no significant interaction between the factors for any of the variables in the two experiments. In the first experiment, egg production was higher with bacterial phytase and egg weight with fungal phytase. The mineral matter showed greater value with 450 FTUs. It is recommended to use bacterial phytase produced from Escherichia coli as it improves the performance of light laying hens. The dosage of 450 FTUs improves the mineral content of light laying hens and the use of phytase in the laying hen diet implies a lower feed cost.